Tác động của bao bì sản phẩm đến giá trị cảm nhận và ý định tiếp tục tiêu dùng đặc sản địa phương - Hoàng Thị Phương, Thảo; Lê Thị Tú, Trâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Local Food is not a beauty of culture but an important economic resource Product packaging is considered as one of the factors reflecting the value of local food The study aims at determining local food packaging attributes and examining their impacts on consumer's perceived value and repurchase intention The study uses Structural Equation Modeling (SEM) and the sample of 259 customers in HCM city, Hanoi, Vungtau, and Dalat Research result indicates three product packaging elements according to consumer perception including: (i) Attractiveness; (ii) Adequate information; and (iii) Convenience These elements have a positive relationship with consumer's perceived value; thereby positively affecting his/her repurchase intention The study also suggests some implications for the improvement of product packaging in order to enhance the consumers' perceived value and then push their behavioral intention of purchasing local food
Keywords: Packaging; Local food; Perceived value; Repurchase intention